Local Wisdom of the Tradition of Pantauan Bunting in the Besemah Tribe in Lahat Regency - Widodo, Sugeng; Istiawati, Novia Fitri; Agustin Lestari, Miranda (Forum Geografi, 2023)
Indonesia is a multi-cultural country characterised by hereditary traditions passed down by ancestors. Strands of this traditional culture are often specific to particular communities, for example the Pantuan Bunting tradition expressed and passed down in the customs of the Besemah community of Lahat Regency, South Sumatra. The purpose of this study is to analyze the social construction of the process of the formation of Pantauan Bunting tradition, the distribution of Pantauan Bunting tradition in different regions, and the existence of Pantauan Bunting tradition in Besemah Tribe community in Lahat Regency. The method used in this study was qualitative with ethnographic, historiographic, and spatial approaches. This research was conducted in three different locations, namely in Kota Agung Village, Penang Village, and Selawi Village where the research subjects consisted of traditional leaders, religious leaders, community leaders, and the Besemah community. The results of this study showed that (1) Pantauan Bunting tradition is constructed by the Besemah community since the time of its earliest ancestors and this process of transmission still continues. This tradition is characterised by a public invitation to prospective brides to come to their prospective bridegrooms’ homes. (2) Pantauan Bunting Tradition has spread to various areas in Lahat Regency, such as Kota Agung Village, Pulau Pinang Village, and Selawi Village. (3) in the modern era, the existence of Pantauan Bunting tradition is maintained by the Besemah community, and we can still find it in various areas in Lahat Regency. The Pantauan Bunting tradition, which has been practised in various parts of Lahat Regency since ancient times and is firmly ingrained in the Besemah community, highlights the community's resiliency and commitment to the preservation of its cultural legacy.